The Influence of Multichannel Marketing towards Purchase Decision in Furniture Industry - Rizkia Nuurul Falah, Amaania; Chaerudin, Rendra (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. These days, the technology development is one of the things that cannot be separated from daily life. Thus, it impacts the marketing channels that being used by the business. The business tends to use several marketing channels or use multichannel marketing, with the focus on the digital channel. Nonetheless, not necessarily all of the business industries are suitable to apply the digital channel, and the business industry that become a concern in this research is the furniture industry. In furniture industry, it needs the customer experience to feel and see the product before the customers decide to buy. In this research, it explores more about the performances of channel in multichannel marketing and how it affects the customerâ€™s purchase decision. The research will be conducted using quantitative approach using questionnaires as the tools with 1-5 point Likert scale. The respondents of the questionnaires are 125 peoples live in Bandung and Jakarta area, and have ever bought the furniture/home dÃ©cor products. Result are being analyzed using multiple regression. Based on result the traditional channel are the most preferred channel among digital and social network channel that influence purchase decision. Hence, the traditional channel is the most powerful channel for furniture business, and the other channel can become the supporting channel.Â Keywords: Digital Channel, Furniture Industry, Multichannel Marketing, Purchase Decision, Traditional Channel